2015
DOI: 10.2217/clp.15.3
|View full text |Cite
|
Sign up to set email alerts
|

The association of dyslipidemia with erythrocyte aggregation

Abstract: Aim:The present study aims to associate erythrocyte aggregation with plasma lipid concentration. Materials & Methods: Ninety-nine participants were divided into two groups: normolipidemic and dyslipidemic. Lipid parameters were measured from serum and erythrocyte aggregation parameters: critical stress and critical time were measured from whole blood. Data were analyzed using IBS SPSS statistics software. Results: Erythrocyte aggregation was higher in the dyslipidemic group when compared with the normolipidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
4
0
3
Order By: Relevance
“…Knowing that hemoglobin affinity for oxygen is not altered during SARS-CoV-2 infection [48] , this decrease in erythrogram parameters may explain in part the need for artificial ventilation experienced by COVID-19 ICU individuals [28] . Considering that, dyslipidemia has been associated with erythrocyte aggregation which may lead to a decreased life span of the cell [49] , our data showing a reduction in erythrogram parameters in severe COVID-19 patients may be related to the reduction in HDL levels, also observed in non-comorbid patients.…”
Section: Discussionsupporting
confidence: 50%
“…Knowing that hemoglobin affinity for oxygen is not altered during SARS-CoV-2 infection [48] , this decrease in erythrogram parameters may explain in part the need for artificial ventilation experienced by COVID-19 ICU individuals [28] . Considering that, dyslipidemia has been associated with erythrocyte aggregation which may lead to a decreased life span of the cell [49] , our data showing a reduction in erythrogram parameters in severe COVID-19 patients may be related to the reduction in HDL levels, also observed in non-comorbid patients.…”
Section: Discussionsupporting
confidence: 50%
“…Park et al (2018) reported that CSS was strongly correlated with acute myocardial infarction in patients with T2DM. CSS has also been found to correlate highly with hyperlipidemia (Gyawali et al, 2015a), chronic inflammatory indexes, and oxidative stress (Gyawali et al, 2015b). Furthermore, Gyawali et al (2014) reported that CSS alone could be used to diagnose metabolic syndrome (MetS) with higher sensitivity and specificity than other conventional indexes such as the ankle brachial pressure index.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Значение морфофункциональных изменений эритроцитов при МС менее изучено, на сегодняшний день в мировой литературе нами не найдено исследований, оцени-вающих состояние ЭЗЭ при МС. В единичных работах показано снижение электрического потенциала эрит-роцитов у больных с АГ, сахарным диабетом и дисли-пидемией [9][10][11][12].…”
Section: Discussionunclassified